The RUTF Biscuit Made From Mung Bean Flour and Anchovy Flour for Stunting Toddlers - Maria Dolorosa Peni Sogen; Ariani Damayanti; Maurice Fengi; Rina Sri Yuliyanti (Window of Health : Jurnal Kesehatan, 2026)
Stunting remains a significant malnutrition issue in Indonesia. According to the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting among toddlers in Central Java is 20.8%, while in Semarang City it is 10.4%. Ready-to-Use Therapeutic Food (RUTF) is an energy-dense, micronutrient-rich product given to toddlers with uncomplicated wasting. Wasting children are three times more likely to become stunted compared to well-nourished children, and stunted children have a 1.5 times greater risk of becoming wasted. The use of RUTF for stunted children has not been extensively studied, particularly regarding formulations that use affordable, nutritious local ingredients. This study aims to develop an RUTF biscuit formulation from mung beans and anchovy flour that is acceptable to toddlers, with appropriate nutritional values and recommended serving sizes. This quantitative experimental study employed a Completely Randomized Design. The objects studied were three treatment groups of RUTF biscuits using mung bean and anchovy flour as substitutes for wheat flour: F2 with 12%, F3 and F4 with 15%, and F1 as a control. Formulation 2, with 10% mung bean and 2% anchovy flour substitution, was the most preferred by panelists, providing energy of 525.60 kcal, fat 25.86 g/100g, carbohydrates 54.73 g/100g, calcium 398.20 mg/100g, and phosphorus 375.63 mg/100g, and passed microbiological contamination tests. However, protein, vitamin C, zinc, and iron levels did not meet the general RUTF and biscuit RUTF standards. With a serving size of 30-40 grams (equivalent to 3-4 pieces), this RUTF biscuit has potential as a locally based supplementary food alternative to support toddler nutritional needs, especially for prevention and recovery from nutritional problems.